ANALISIS FREKUENSI KONSUMSI MAKANAN LAUT DAN KANDUNGAN LOGAM BERAT Pb DALAM DARAH WANITA USIA SUBUR (WUS) DI WILAYAH KERJA PUSKESMAS BANDARHARJO - Dini Kusumastuti; Onny Setiani; Tri Joko (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2020)
Bandarharjo is one of Semarang coastal area which has a surrounding industrial area, so it could potentially be a source of heavy metals Pb polluting waters. Through the process of bioaccumulation, Pb is absorbed by sea creatures such as fish, shellfish and shrimp. Continuous exposure to Pb over a long period of time can cause negative effects to health such as hypertension, regulating, the reproductive system and nervous system. The purpose of this study is to analyze the relationship between seafood consumption and blood levels of Pb in women of childbearing age in the working area of Bandarharjo Public Health Center, North Semarang District, Semarang City. This type of research is analytic descriptive by discussing cross sectional study. The sample in this study were 34 childbearing. Data collection was carried out through interviews, observations, and laboratory examinations of Pb levels in the blood. Data analysis using Chi-square test. The results of univariate analysis found 15 respondents (44,1%) had a frequent category ≥ 4 times a week of seafood consumption and 19 respondents (59,9%) had Pb levels in their blood with excessive information based on examination results ranging from mean ≥ 77,02 µg/dL. The results of bivariate analysis is the frequency seafood consumption with blood levels of Pb (p-value = 0,012) with a Prevalence Ratio = 2,171 with 95% Confidence Interval 1,144 – 4,121. The conclusion of this study is that there is a significant relationship between the frequency seafood consumption with blood levels of Pb childbearing in the Bandarharjo Public Health Center.